The Effect of Enhanced External Counterpulsation Therapy and Improvement of Functional Capacity in Chronic Heart Failure patients: a Randomized Clinical Trial - Starry H Rampengan; Joedo Prihartono; Minarma Siagian; Suzanna Immanuel (Acta Medica Indonesiana, 2015)
Aim: to investigate the efficacy of enhanced external counterpulsation (EECP) therapy to improve functional capacity in patients with chronic heart failure (CHF). Methods: a double-blind random clinical trial was performed in 99 patients with CHF who had received EECP therapy at Jade Cardiovascular Clinic, Manado, North Sulawesi, Indonesia between January 2014 and June 2015. Subjects were categorized into 2 groups, i.e. 49 subjects had sham EECP therapy and 50 subjects had EECP therapy. All subjects performed six-minute walking test (6MWT) before and after receiving EECP therapy. Results: there was no significant difference between both groups regarding the basic characteristics of patients with CHF. The 6MWT result before EECP therapy showed that there were 30 patients (61.2%) with walk distance of <300 meter in the sham EECP group; while in the group receiving EECP therapy, we found 34 patients (68%); p=0.24. Post-EECP therapy, there were 33 patients (67.3%) with walk distance of <300 meters in EECP sham group; while in the group receiving EECP alone, there was only 1 patient (2%); p <0.01.The 6MWT walk distance in sham group before EECP therapy was 252.65 (SD 97.55) meters and it was 243.65 (SD 86.96) meters following the EECP therapy; p=0.18. In EECP group, the 6MWT walk distance before therapy was 256.88 (SD 85.56) meters and after EECP therapy the walk distance was 449.46 (SD 92.08) meters; p<0.01. Conclusion: EECP therapy is effective to improve functional capacity in patients with CHF.